Basin of attraction of triangular maps with applications - Cima, Anna; Gasull, Armengol; Mañosa, Víctor (Journal of difference equations and applications, 2014)
We consider planar triangular maps . These maps preserve the fibration of the plane given by . We assume that there exists an invariant attracting fibre for the dynamical system generated by φ, and we study the limit dynamics of those points in the basin of attraction of this invariant fibre, assuming that either it contains a global attractor or it is filled by fixed or two-periodic points. We apply our results to several examples.